Sicily: Gateway to the Spread of Islam to Europe - Sugiarto, Danu (CV Kalimasada Group, 2024)
The spread of Islamic Civilization to European territories occurred through various means, including territorial conquest. One of the conquests that played an important role in the spread of Islamic religion and civilization was the conquest of the island of Sicily. This research aims to describe the history of the arrival of Islam to Sicily and the progress of civilization that resulted as well as the factors of the collapse of Islamic civilization in Sicily. This research is a type of qualitative research with a literature study approach. Research data is obtained from books, journals and scientific works that are relevant to the research objectives. The results of the research show that Muslims succeeded in controlling Sicily in 902 M. The contribution of Islamic civilization to Sicily included improving the community's economy resulting from agricultural and industrial systems. Apart from that, the contribution of Islamic civilization in Sicily is demonstrated by advances in science such as physics and medicine. Meanwhile, the collapse of Islamic civilization in Sicily occurred since 1040 M due to divisions which led to the emergence of petty kings known as qa'id in various regions of the island of Sicily